Rigid docking application to investigate sulfonylurea family members’ binding site with their receptor kir6.2sur1 (Funded work) - FARAH YOUSEF; OUSSAMA MANSOUR; JEHAD HERBALI (International Journal of Pharma and Bio Sciences, 2019)
Sulfonylurea family members have been used as a second preferred line in the treatment of Type II Diabetes Mellitus (TIIDM) for decades. Only one crystal structure for its receptor Kir6.2 SUR1 binding with one of sulfonylurea member; Glibenclamide (GBM), is available in Protein Data Bank (PDB) database. The aim of this manuscript is to study in-silico other sulfonylurea family members’ inter actions with their receptor Kir6.2 SUR1 using a docking software in the default settings. We have checked the validity of the software for the study. Then, rigid docking had been applied on 14 compounds of sulfonylurea group which they have anti-hyperglycemia activity. Next, we have compared their interactions to GBM interactions with Kir6.2 SUR1. As a result, many compounds of this family had bound to Kir6.2 SUR1 receptor in the same pocket as GBM. These results confirmed a perspective we have discussed about sulfonylurea structure activity relationship.